Surgical management of primary mediastinal mature teratoma: A single-center 20 years’ experience - Zhang, Zhedong; Wang, Xun; Zhou, Zuli; Jiang, Guanchao; Li, Yun (Frontiers in Surgery, 2022)
Background: This study aimed to investigate the clinical efficacy of video-assisted thoracic surgery (VATS) in treating mediastinal mature teratoma (MMT) and explore the clinical factors that increase the difficulties associated with VATS. Method: We retrospectively reviewed 101 consecutive patients with MMT who underwent surgical excision between November 2001 and June 2021. Follow-up was completed by telephone or outpatient clinic. The deadline for follow-up was February 2022. Results: The operative time, the chest tube indwelling time and the hospital stay duration were significantly shorter in the VATS group compared to the thoracotomy group. The intraoperative and postoperative complication rates in VATS were lower than thoracotomy group (P＜0.05). In thoracoscopic surgery, the clinical symptoms during the course of the disease were significantly associated with bleeding loss increasing (OR = 3.562; 95% CI 1.180 - 10.753, P = 0.024) and operation time extension (OR = 5.697; 95% CI 1.529 - 21.221, P = 0.010). The relationship between lesions and superior vena cava (SVC) or innominate vein (IV) from preoperative CT imaging was significantly associated with bleeding loss increasing (OR = 4.629; 95% CI 1.463 - 14.639, P = 0.009). A maximal lesion diameter greater than 7 cm was significantly associated with increased risks of operation time extension (OR = 5.019; 95% CI: 1.641 - 15.348, P = 0.005). Conclusion: Compared with traditional thoracotomy surgery, VATS can be performed safely in selected patients with MMT. A surgical method for complete resection needs to be determined according to preoperative imaging and intraoperative conditions to reduce the unnecessary damage.